Strengthening the Tourism Village Program: Educational Tourism on Waste Bank and Clean and Healthy Living Behavior - Khambali; Rachmaniyah; Fitri Rokhmalia; Yessy Dessy Arna (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Sawahan Village, Watulimo Subdistrict, Trenggalek Regency, is one of the tourist village areas developed by the local community. Several tourism programs have been established by the local tourism awareness groups, including durian forest tourism. In 2023, a chlorine diffuser technology was implemented to support the development of the tourist village, ensuring access to clean water. This appropriate technology is not only designed to produce clean water but also serves as a strategy to meet the requirements of Clean and Healthy Behavior (CHB). In 2024, community service has focused more on waste management through a waste bank. The methods employed include Focus Group Discussions (FGD) on educational tourism through waste banks, education on the separation of organic and inorganic waste, and community assistance with Clean and Healthy Behavior (CHB). The activities conducted resulted in increased community knowledge about waste banks, from 10 people (10%) to 48 people (96%). Not only did the community's knowledge improve, but their behavior also changed, with the creation of separate waste containers for organic and inorganic waste increasing from 3 people (6%) to 38 people (76%). Additionally, the community's behavior regarding clean and healthy living improved, with handwashing facilities available in every home and throughout the tourist area, reaching 50 people (100%). These changes in knowledge and behavior indicate that community service activities can only succeed with the community's willingness and ability to achieve sustainability and self-sufficiency.